Respuesta :

For this case we have the following expression:

[tex]2x * 3x ^ 2 =[/tex]

By definition of multiplication of powers of the same base, we have to put the same base and add the exponents, that is:

[tex]a ^ n * a ^ m = a ^ {n + m}[/tex]

So:

[tex]2x * 3x ^ 2 = (2 * 3) x^{1 + 2} = 6x ^ 3[/tex]

Answer:

[tex]6x ^ 3[/tex]

Answer: [tex]6x^3[/tex]

Step-by-step explanation:

You need to remember a property called "Product of powers property". This property states the following:

[tex](a^m)(a^n)=a^{(m+n)}[/tex]

In this case you can observe that the bases of the expression [tex]2x*3x^2[/tex] are equal, this means that you can apply the property mentioned before.

Knowing this you can make the multiplication.

Then, the product you get is:

[tex]2x*3x^2=6x^{(1+2)}=6x^3[/tex]